Automated opportunistic screening for osteoporosis using deep learning-based automatic segmentation and radiomics on proximal femur images from low-dose abdominal CT - Changyu Du; Jian He; Qiye Cheng; Mengting Hu; Jingyi Zhang; Jiageng Shen; Shigeng Wang; Yijun Liu; Jianying Li; Wei Wei (BMC Musculoskeletal Disorders)
Abstract Rationale and objectives To establish an automated osteoporosis detection model based on low-dose abdominal CT (LDCT). This model combined a deep learning-based automatic segmentation of the proximal femur with a radiomics-based bone status classification. Materials and methods A total of 456 participants were retrospectively included and were divided into a development cohort comprising 355 patients, with a 7:3 ratio randomly assigned to the training and validation cohorts, and a test cohort comprising 101 patients. The automatic segmentation model for the proximal femur was trained using VB-Net. The Dice similarity coefficient (DSC) and volume difference (VD) were employed to evaluate the performance of the segmentation model. A three-classification predictive model for assessing bone mineral status was constructed utilizing radiomic analysis. The diagnostic performance of the radiomics model was assessed using the area under the curve (AUC), sensitivity, and specificity. Results The automatic segmentation model for the proximal femur demonstrated excellent performance, achieving DSC values of 0.975 ± 0.012 and 0.955 ± 0.137 in the validation and test cohorts, respectively. In the test cohort, the radiomics model utilizing the random forest (RF) classifier achieved AUC values, sensitivity, and specificity of 0.924 (95% CI: 0.854–0.967), 0.846 (95% CI: 0.719–0.931), and 0.837 (95% CI: 0.703–0.927) for the identification of normal bone mass. For the identification of osteoporosis, the corresponding metrics were 0.960 (95% CI: 0.913-1.000), 0.947 (95% CI: 0.740–0.999), and 0.963 (95% CI: 0.897–0.992). In the case of osteopenia, the corresponding metrics were 0.828 (95% CI: 0.747–0.909), 0.767 (95% CI: 0.577–0.901), and 0.746 (95% CI: 0.629–0.842). Conclusion A three-classification predictive model combining a deep learning-based automatic segmentation of the proximal femur and a radiomics-based bone status classification on LDCT images can be used for the opportunistic detection of osteoporosis.